A Comparative Analysis of Health Science Student Understanding of Statistical Tables - Alonso Ricardez, Abraham (2026)
This study assessed the competence and overall performance of health science students in reading and understanding statistics tables using an observational, cross-sectional, prospective, and correlational methodology. A non-probabilistic sample of 151 students was selected from five undergraduate programs: Biology, Nursing, Medicine, Optometry, and Psychology, with roughly 30 students in each cohort. Two outcomes were evaluated: the competence level, which measures how well a student can read, compare, deduce, and critique information in a statistical table, and a comprehensive score, which is based on the total number of correct answers across tasks of different levels of difficulty, with a complexity factor used to weigh the scores. The results indicated that 95.4% of students could comprehend factual information in a table, 78.1% were able to analyze data and make judgments, 26.5% could deduce unspoken information, and 42.4% could critique the material presented. The ability to infer knowledge was strongly linked to their having been accepted for Biology programs (p = 0.001). Biology students ranked well in all four levels of difficulty. Biology and Psychology students had the highest overall scores which were statistically significantly different (p = 0.017) from Nursing, Optometry, and Medical students. Performance discrepancies seem to be related to differences in the curriculum. Certain Biology and Psychology classes, for example, teach statistical content and data inference from statistical tables. The findings indicate that students across diverse health disciplines exhibit significantly varying competencies in reading and comprehending statistical tables. This indicates that classes emphasizing statistical content, rather than solely on research project development, can enhance student comprehension and interpretation of the topic. Modifications to the curriculum of Nursing, Optometry, and Medicine may also be warranted to this end.